Principals' Technology Leadership: How a Conceptual Framework Shaped a Mixed Methods Study. Issue 5 (September 2016) - Brown, Barbara; Jacobsen, Michele
A multifaceted conceptual framework of principals' technology leadership informed the design of a mixed methods case study exploring leadership practices across three school jurisdictions in Alberta, Canada. Leadership practices of K-12 school principals involved in making school-wide improvements integrating technology were examined The intent of this article is to discuss how the conceptual framework influenced the research process as an interconnection of learning theory based on the learning sciences, transformative knowledge-building pedagogies, and the complexities for school leaders as they cultivate a growth-oriented culture. Findings are related to three key areas: (1) leadership preparation is needed in instructional leadership and technological fluency; (2) online networks can support professional learning; and (3) practitioner–researcher partnerships can support innovation in schools.